Estimating the economic value of climate services for strengthening resilience of smallholder farmers to climate risks in Ethiopia: A choice experiment approach - Tesfaye, Abonesh; Hansen, James; Kassie, Girma T.; Radeny, Maren A.O.; Solomon, Dawit (Elsevier, 2019)
This study estimated the economic value of agricultural climate services for strengthening the resilience of smallholder farmers to climate variability and risks in Ethiopia. Using a choice experiment approach, the study introduced a hypothetical package of improved climate services to 600 randomly selected smallholder farmers in three districts across three different agro-ecological zones in the Oromia Regional State. A generalized multinomial logit (G-MNL) model was used to estimate preferred attributes of climate services and willingness-to-pay (WTP) values. The results show that the preferred bundle of improved climate services among smallholder farmers was one that could be communicated in short text message system, provided along with credit facility, and market information and one that favors participatory decision making by smallholders. The results further reveal that the WTP value exhibited high implicit price for participatory decision-making. The study sheds light on important characteristics of agricultural climate services that may improve their acceptability and usability among smallholders. It also highlights the importance of packaging additional services including digital and ICT-based solutions, financial and market information along with climate services to promote demand-driven last mile delivery systems. Engaging smallholder farmers in a participatory manner in the decision-making process can help them make informed decision.